EPISTEMOLOGI ISLAM INTEGRATIF: ANALISIS KOMPREHENSIF EMPAT SUMBER ILMU (PANCA INDRA, AKAL, WAHYU, DAN ILHAM) - Dewi Maharani; Budi Handrianto; Hasbi Indra (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
The study of Islamic epistemology is increasingly significant in the context of the dominance of modern scientific paradigms that tend to be reductionist and emphasize empiricism and rationalism as the sole legitimate sources of knowledge. Such an orientation has led to the separation of science from moral and spiritual values. This article aims to analyze comprehensively the four sources of knowledge in Islamic epistemology sense perception, reason, khabar ṣādiq (true testimony), and inspiration (ilham)and to explain their integrative structure within an Islamic epistemological framework. This study employs a qualitative approach using library research methods by examining and critically analyzing relevant classical and contemporary literature, including scholarly books and peer-reviewed journal articles. The research stages consist of source collection, conceptual classification, comparative analysis, and epistemological synthesis. The findings reveal that Islamic epistemology does not absolutize a single source of knowledge; rather, it positions the four sources within a layered epistemic structure according to their respective objects of inquiry, namely physical, rational, metaphysical, and inner-spiritual realities. The main conclusion of this study affirms that integrative Islamic epistemology offers a holistic and balanced paradigm of knowledge that harmonizes empirical data, rational analysis, revelatory authority, and spiritual experience. This paradigm has significant implications for the development of Islamic education and scientific inquiry that aim not only at intellectual advancement but also at moral and spiritual formation. ABSTRAK Kajian epistemologi Islam menjadi penting di tengah dominasi paradigma ilmu modern yang cenderung reduksionistik dan menempatkan empirisme serta rasionalitas sebagai satu-satunya sumber pengetahuan yang sah. Kondisi ini berimplikasi pada pemisahan antara ilmu, nilai, dan spiritualitas dalam pengembangan pengetahuan dan pendidikan. Artikel ini bertujuan menganalisis secara komprehensif empat sumber ilmu dalam epistemologi Islam, yaitu pancaindra, akal, wahyu atau khabar ṣādiq, dan ilham, serta menjelaskan pola integrasinya dalam membangun paradigma epistemologi Islam integratif. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kepustakaan (library research) melalui penelusuran dan analisis kritis terhadap literatur klasik dan kontemporer yang relevan, meliputi buku akademik dan artikel jurnal ilmiah. Tahapan penelitian meliputi pengumpulan berbagai sumber otoritatif, klasifikasi konsep epistemik, analisis komparatif, dan sintesis konseptual. Hasil penelitian ini menunjukkan bahwa epistemologi Islam tidak memutlakkan satu sumber pengetahuan, melainkan menempatkan keempat sumber ilmu tersebut dalam struktur epistemik berlapis sesuai dengan objek kajiannya, yaitu realitas fisik, rasional, metafisik, dan batiniah. Adapun kesimpulan utama artikel ini menegaskan bahwa epistemologi Islam integratif menawarkan kerangka pengetahuan yang holistik dan seimbang, yang berpotensi menjadi dasar pengembangan ilmu dan pendidikan Islam yang tidak hanya berorientasi pada kecerdasan intelektual, tetapi juga pembentukan moral dan spiritual manusia.